L’effort de guerre des exploitants non-professionnels du cinéma en URSS (1939-1949) - Irina Tcherneva (Conserveries Mémorielles)
The history of Trade union and corporate networks that occasionally use cinema in the USSR has not yet been written. This paper is specifically aimed at introducing the Soviet case into historiography, devoted to the use of cinema by churches, political parties and trade unions in European countries. If the educational approach and the project of spreading ideas through films resonate particularly in the Soviet Union, the trajectory of these non-professional film exhibitors is singular. It is so in view of the context of the planned economy and the subordination of trade unions and enterprises to political power. Moreover, the Soviet film administration implements a policy that ultimately leads to the professionalisation of these networks. This article focuses on the turning point that occurred as early as 1939, and on two paradoxical effects that it triggered in the immediate post-war period. On the one hand, the Ministry of Cinema is struggling to control the financial transactions in union and corporate cinemas. On the other hand, this new nature of a priori educational exhibitors proves to be an impasse for propaganda through film.